Relation between heterozygote state of vascular endothelial growth factor (VEGF) gene polymorphism and bone mineral density - Deveci, Derya; Ozkan, Zehra Sema; Kumbak, Banu; Yuce, Huseyin (Elsevier Sci Ltd, 2011)
[Abstract Not Available]
European Biotechnology Congress -- SEP 28-OCT 01, 2011 -- Istanbul, TURKEY